Effect of Turmeric Ethanol Extract (Curcuma Longa Linn.) on Tumor Necrosis Factor alpha (TNFα) and the extent of wound lesions (Experimental Study on Wistar Rats Exposed to UVB Rays) - Rahim, Denasa Dwi Sopandita; Sumarawati, Titiek; Chodidjah; Zulaikhah, Siti Thomas; Priyantini, Sri; Trisnadi, Setyo (Gema Lingkungan Kesehatan, 2025)
Continuous exposure to ultraviolet B (UVB) radiation can induce photoaging and accelerate premature skin aging. Turmeric (Curcuma longa) is a medicinal plant that contains curcumin, an active compound known for its anti-inflammatory properties and its role in accelerating wound healing. This study aimed to evaluate the effect of turmeric ethanol extract on TNF-α levels and wound lesion areas in Wistar rats exposed to UVB radiation. A post-test-only control group design was employed, involving 24 Wistar rats divided into four groups: a healthy control group (K1), a negative control group (K2), and two treatment groups receiving oral turmeric ethanol extract at doses of 100 mg/kg BW (K3) and 200 mg/kg BW (K4) for 14 days, with concurrent UVB exposure. TNF-α levels were assessed using one-way ANOVA followed by Tukey's post hoc test, while wound lesion areas were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney U test. The results showed that the highest TNF-α levels were observed in the healthy control group (129.14 ng/L), although no statistically significant differences were found between groups (p = 0.538). In contrast, a significant difference was observed in wound lesion areas (p < 0.001), with the largest lesions occurring in the negative control group. In conclusion, oral administration of turmeric ethanol extract did not significantly affect TNF-α levels but was effective in reducing the area of wound lesions caused by UVB exposure.